Prevalence of and factors associated with sarcopenia among multi-ethnic ambulatory older Asians with type 2 diabetes mellitus in a primary care setting - Fung, Foon Yin (BMC Geriatr, 2019)
BACKGROUND: Sarcopenia is the age-related loss of muscle mass and function, which increases fall risks in older persons. Hyperglycemia relating to Type-2 Diabetes Mellitus (T2DM) is postulated to aggravate sarcopenia. This study aimed to determine the prevalence of sarcopenia among ambulatory community-dwelling older patients, aged 60–89 years, with T2DM in a primary care setting and to identify factors which mitigate sarcopenia. METHODS: A total of 387 patients were recruited from a public primary care clinic in Singapore. Data on their socio-demography, clinical and functional status, levels of physical activity (International Physical Activity Questionnaire) and frailty status was collected. The Asian Working Group for Sarcopenia (AWGS) criteria were used to define sarcopenia based on muscle mass, grip strength and gait speed. RESULTS: The study population comprised men (53%), Chinese (69%), mean age = 68.3 ± SD5.66 years, lived in public housing (90%), had hypertension (88%) and dyslipidemia (96%). Their mean muscle mass was 6.3 ± SD1.2 kg/m(2); mean gait speed was 1.0 ± SD0.2 m/s and mean grip strength was 25.5 ± SD8.1 kg. Overall, 30% had pre-sarcopenia, 24% with sarcopenia and 4% with severe sarcopenia. Age (OR = 1.14; 95%CI = 1.09–1.20;p < 0.001), multi-morbidity (OR = 1.25;95%CI = 1.05–1.49;p = 0.011) diabetic nephropathy (OR = 2.50;95%CI = 1.35–5.13;p = 0.004), hip circumference (OR = 0.86;95%CI = 0.82–0.90;p < 0.001) and number of clinic visits in past 1 year (OR = 0.74; 95%CI = 0.59–0.92;p = 0.008) were associated with sarcopenia. CONCLUSIONS: Using AWGS criteria, 58% of older patients with T2DM had pre-sarcopenia and sarcopenia. Age, diabetic nephropathy, hip circumference, multi-morbidity and fewer clinic visits, but not a recent single HBA1c reading, were significantly associated with sarcopenia among patients with T2DM. A longitudinal relationship between clinic visits and sarcopenia should be further evaluated. (250 words)